2015
DOI: 10.1089/neu.2014.3787
|View full text |Cite
|
Sign up to set email alerts
|

Associations between Muscle Strength Asymmetry and Impairments in Gait and Posture in Young Brain-Injured Patients

Abstract: Traumatic brain injury (TBI) can lead to deficits in gait and posture, which are often asymmetric. A possible factor mediating these deficits may be asymmetry in strength of the leg muscles. However, muscle strength in the lower extremities has rarely been investigated in (young) TBI patients. Here, we investigated associations between lower-extremity muscle weakness, strength asymmetry, and impairments in gait and posture in young TBI patients. A group of young patients with moderate-to-severe TBI (n=19; age,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
11
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(12 citation statements)
references
References 47 publications
1
11
0
Order By: Relevance
“…Furthermore, grip strength also requires far less neural recruitment being a more isolated movement that requires less coordination for a smaller body region and therefore decreased performance may resolve more quickly following concussion. Previous research on youth with a moderate to severe TBI revealed a decrease in strength and an increase in strength asymmetry compared to healthy controls [6], which supports the observation that muscle weakness may occur as a result of impairment in neurological function following a brain injury.…”
supporting
confidence: 78%
“…Furthermore, grip strength also requires far less neural recruitment being a more isolated movement that requires less coordination for a smaller body region and therefore decreased performance may resolve more quickly following concussion. Previous research on youth with a moderate to severe TBI revealed a decrease in strength and an increase in strength asymmetry compared to healthy controls [6], which supports the observation that muscle weakness may occur as a result of impairment in neurological function following a brain injury.…”
supporting
confidence: 78%
“…According to our knowledge, this is the first study that assessed lower limb strength asymmetry in HIV-positive subjects, although these differences have also been observed in other populations, such as older adults 10 and subjects with multiple sclerosis 12 and traumatic brain injury. 11 …”
Section: Discussionmentioning
confidence: 99%
“…Previous studies with other populations demonstrated an association between muscle strength asymmetry and impaired balance or gait. Drijkoningen et al 11 demonstrated that increased asymmetry in muscle strength between D and ND limbs was associated with poorer balance control and a more variable and asymmetric gait. It is believed that, over time, an impaired balance and gait could lead to muscle imbalance, probably because the subject exerts more strength in one of the limbs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been suggested that a decrease in the ability to generate force in the lower extremity muscles contributes to standing balance impairment [3]. A deficit in lower extremity muscle strength symmetry (knee flexor/extensor) has been identified as one of the most important intrinsic factors associated with lower extremity injuries and a risk factor for impairment in control of standing posture and gait [4]. Due to its importance, PS and/or lower extremity strength were considered to be significant components required to facilitate age-related deficits related to fall prevention or rehabilitative intervention programs in individuals [5].…”
Section: Introductionmentioning
confidence: 99%